Analisis Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Mie Gacoan Cikarang - Dela Dewi Permata; Sabrina Malakiano; Muhammad Sadam; Ega Radiansyah; Daffa Nur Syahidah (Global Leadership Organizational Research in Management, 2025)
This study aims to analyze the impact of product quality and service quality on customer satisfaction at Mie Gacoan Cikarang. The identified problem in this study is how these two factors influence customer experience and loyalty to the restaurant. This research uses a descriptive qualitative method with a case study approach, where data was collected through in-depth interviews with customers and direct observations at the location. Based on the analysis, product quality, including taste, texture, and consistency, has a significant impact on customer satisfaction, with 80% of respondents expressing satisfaction with the products offered. Additionally, service quality, which includes speed, efficiency, and staff friendliness, also plays an important role in creating a positive experience for customers. The results of this study indicate that improving both product and service quality directly contributes to customer satisfaction and has the potential to increase customer loyalty. These findings provide recommendations for Mie Gacoan Cikarang management to maintain and enhance product and service quality in order to strengthen customer attraction and loyalty.